A pilot application of a questionnaire to evaluate visually induced motion sickness in spectators of tri-dimensional (3D) movies (Italian Journal of Public Health, 2011)
Background: The increasing popularity of tri-dimensional (3D) movies has raised public concern and media interest about the safety of projected images for spectators. No specific instrument exists to assess the occurrence of visually induced motion sickness (VIMS) symptoms in 3D movie spectators in movie theaters.Methods: We developed a questionnaire containing 20 items divided into socio demographics, individual characteristics, movie vision characteristics and VIMS symptoms (during, right after, and at two hours from the viewing of the movie ). The questionnaire was self administered to 38 subjects, asking them to report time taken for its completion, comments and eventual difficulties in interpreting items.Results: Poor understanding or problems in identifying the correct item choice were noted for 4 questions belonging to the socio demographics section that were simplified in the final version of the questionnaire. Two other questions were merged into one after homogeneity analysis. Most VIMS symptoms were observed during the movie and quickly thereafter. Tired eyes was the symptom most often reported (39.5% of responders) followed by headache (18.4%), dizziness (18.4%) and nausea (15.8%). Double vision and palpitation were reported with very low frequency (respectively 5.3% and 2.3%) and vomit was not reported by any respondent. Homogeneity of symptom items was good (Cronbach alpha= 0.69). Reliability analysis showed satisfactory item-total correlations (alpha coefficient ranging from 0.61 to 0.73).Conclusions: The refined survey questionnaire can be applied in future studies to assess the frequency of VIMS symptoms in spectators of 3D movies and to identify the risk factors connected to inter-individual differences in susceptibility and to the characteristics of the movie viewing.
Keywords: visually induced motion sickness; questionnaire; tridimensional 3D movies